Specific Kaliningrad character of the Russian identity - Klemeshev Andrey; Fedorov Gennady; Fidrya Efim (Bulletin of Geography. Socio-Economic Series, 2017)
There are different levels of territorial identity perceived as a sense of belonging to a particular social and territorial community. People residing in any region identify themselves with these levels to a different degree. Since 2001, the authors have been doing sociological research into the territorial identity of the population of the Kaliningrad region, which became a Russia’s exclave after the demise the USSR. The research shows that residents of the Kaliningrad region associate themselves with different territorial communities to a varying degree starting with an ever strengthening sense of national identity, followed by the regional and local identity. The sense of macro-regional (European) and global identity is significantly lower.